Konseling dalam Bai’at Tarekat Shiddiqiyyah (Jurnal Bimbingan dan Konseling Islam, 2021)
This article explores the counseling aspects of Tariqa Shiddiqiyyah bai’a. Whereas, the bai’a of tariqa can effectively form a counscious personality (ma’rifat) that is present in Allah’s environtment so that a militant attitude emerges in doing worship. The main question is what are the values of counseling in the bai’a of Shiddiqiyyah Tariqa? How to use tariqa bai’a in counteracting extremism and radicalism? This research was carried out qualitatively which made bai’a of tariqa the main data collected through involved observation, in-depth interview, and documentation. The collected data were analyzed using phenomenological interpretation techniques. The results show; first, bai’a of the tariqa of Shiddiqiyyah is a murshid discourse to his students to be intensive in reciting dhikr; the murshid or caliph always guides and accompanies the student in dhikr, so that the student must present in imaginary murshid figure in him self when doing dhikr. Seond, the bai’a of Shiddiqiyyah tariqa teaches the unity of the servant with God, namely, 1) Shiddiqiyyah students must identify with the attributes of Allah as Almighty Who always works hard to provide sustenaince and protect His servants, 2) Students of Shiddiqiyyah tariqa position themselves as servants who are guided by ‘Gusti’ Allah, The Lord of The Most excellency of the King, so that they are diligent in working to achieve His blessings and mercy. So, the bai’a of Shiddiqiyyah tariqa is projected to guide the tariqa students in order to synergize between true faith in Allah with the spirit of working as worship to gain the benefit of life. On that basis, the bai’ah of tariqa creats militancy for work and worship which also has the potencial to ward off the militancy of terrorists who fail to understand in doing God services.